MATERIALITY - AN IMPORTANT METHOD AND TECHNIQUE FOR THE FINANCIAL AUDITING - Pjeter Ndreca (European Scientific Journal, ESJ, 2013)
The purpose of this press article is:- to address the application of materiality in nature as one of the best techniques that provides assurance in auditing the financial statements,- to precise the concept of materiality and his definition,- to explain the relationship and difference that exist between materiality and the auditing risk,- to explain the procedures to be followed in determining the assurance factor,- to prove that the best efficiency in auditing financial statements, can be achieved if we apply materiality in nature,- to explain the nature of indicators and the method of calculating,- to illustrate through a practical case the methodology for calculating the indicators of materiality in nature and to interpret the data in comparison of indicators.